Fostering Data Literacy and Environmental Awareness among Students through Statistics Education at SMAN 1 Sipoholon - Simatupang, Limmarten; Marpaung, Rony; Rida Gultom; Dostri Ambarita; Yulia Kurnia Sari Sitepu; Eduward Hutabarat; Maringan Sinambela (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Data literacy and environmental awareness are essential competencies for students in responding to contemporary social and environmental challenges. However, the integration of statistical education with real-life environmental contexts remains limited in many secondary schools. This community service program aimed to foster data literacy and environmental awareness among students at SMAN 1 Sipoholon through statistics-based educational activities. The program was conducted on 10 October 2025 and involved 25 participants consisting of students, internal participants, organizers, and a resource person. The implementation was carried out through two main stages: (1) training and capacity building in basic statistical concepts, and (2) reward-based question-and-answer activities to reinforce learning outcomes. Data were collected using pre- and post-activity questionnaires, observation sheets, and analysis of student responses during interactive sessions. The results indicate an improvement in students’ understanding of basic statistical concepts, increased engagement during learning activities, and enhanced awareness of the role of data in interpreting environmental issues. Positive responses from teachers and students highlight the effectiveness of contextual and participatory learning approaches supported by lecturer and university student mentoring. Despite limitations related to time and learning resources, the program demonstrated promising outcomes and offers a replicable model for similar educational contexts. This community service initiative contributes to the promotion of quality education and environmental awareness in alignment with the Sustainable Development Goals (SDGs).